Mеthods of classification of phraseologisms on lexical and grammatical features - Рысбaев, А. Б.; Теменовa, Г. К.; Нaзaровa, А. Ж. (Journal of Oriental Studies, 2018)
Phraseologisms are one of the most significant units in the language. The phraseological foundation of any language is very rich and diverse. Turkic languages are rich with phraseological units and are often used in various spheres of life. For free communication in a foreign language it is necessary to have a phraseological stock. The significance of learning of lexico-semantic signs of phraseological stock in foreign language and their ways of comparison with materials in mother tongue are considered in this article.